Changing Use of Seventh Chords: A Replication of Mauch et al. (2015) - L, Hubert (Empirical Musicology Review, 2016)
Mauch, MacCallum, Levy, and Leroi (2015) carried out a large-scale study of changes in American popular music between 1960 and 2010. Using signal processing methods, they found evidence suggesting a decreasing use of the dominant seventh chord and increasing use of the minor-minor seventh chord. While signal analysis methods have improved substantially in recent years, the accuracy of signal-based analysis remains imperfect. Using a contrasting method and independent musical sample, this paper reports converging evidence replicating these findings.